Significance of arylsulfatase A in spermatogenesis and sperm fertilizing ability - Xu, Hongbin (University of Ottawa (Canada), 2009)
We have previously shown that arylsulfatase A (ASA), present on the sperm head surface, is involved in sperm-zona pellucida (ZP) binding in vitro. Here, I described how ASA, usually known as an acrosomal enzyme without a transmembrane domain, trafficked to the sperm head surface. In the testis, ASA was localized to the developing acrosomal granules of spermatogenic cells as well as late residual bodies of Sertoli cells. However, the roles of ASA in these entities are unknown. ASA was also secreted by the cauda epididymis and vas deferens, resulting in its localization to the sperm plasma membrane overlying the acrosome, a mechanism dependent on the affinity of ASA to the sperm plasma membrane sulfogalactosylglycerolipid (SGG). Purified sperm ASA bound directly to the ZP3 and ZP2 sulfoglycoproteins, suggesting a role of sperm surface and acrosomal ASA in the primary and secondary sperm-ZP binding, respectively. I further characterized the fecundity of ASA null males to verify the roles of sperm ASA in fertilization in vivo and to investigate the functions of ASA in the testis. The ASA null mice exhibited normal sperm fertilizing ability and spermatogenesis when they were less than 5 months old. However, when they reached 8 months of age, their sperm fertilizing ability was almost zero. The spermatogenesis was also perturbed with significantly increased number of apoptotic germ cells. Since SGG is expressed in male germ cells, and it can be desulfated by ASA in vitro, accumulation of SGG in the testis and sperm of ASA null mice was expected. By using a very sensitive quantitative ESI-MS with a proper internai standard (deuterated SGG), the amount of SGG in sperm of 8-month-old mutant mice was found to be significantly reduced, while no significant changes were detected in 5-month-old KO mice. Although these results were contradictory to what was expected, they may explain, at least in part, the reduced sperm fertilizing ability of the older mutant mice SGG is involved in sperm-egg interaction). As expected, SGG was indeed accumulated in the testis of ASA null mice at both ages. Consistent with the SGG quantification data on sperm, the levels of SGG in testicular germ cells, analyzed by flow cytometry using affinity-purified anti-SGG IgG, were found to be reduced only in 8-month-old ASA null mice, compared with age-matched WT. These results suggested that SGG was unlikely to be accumulated in testicular germ cells. Rather, the sulfoglycolipid might be accumulated in Sertoli cells owing to their phagocytotic activity toward membrane remuants of apoptotic germ cells and residual bodies, which should contain SGG. Palmitoylsulfatide, a sulfoglycolipid not normally present in WT testis at an appreciable amount, was also found to be accumulated in the mutant testis. The accumulation of SGG and other sulfoglycolipids in the testis (in Sertoli cells by deduction) may impair cellular functions, leading to aberrant sperm SGG levels and disruption of spermatogenesis. In conclusion, ASA is important for keeping the balance of SGG in the testis and sperm, which is important for spermatogenesis and sperm fertilizing ability.
Keywords: Chemistry, Biochemistry.